Prenatal care in high-risk pregnancies and associated factors in the city of Sao Paulo, Brazil - Sanine, Patricia Rodrigues [UNESP]; Venancio, Sonia Isoyama; Gonzaga da Silva, Fernanda Luz; Aratani, Nathan; Garcia Moita, Maria Lucia; Tanaka, Oswaldo Yoshimi (Cadernos Saude Publica, 2019)
This study assessed prenatal care in high-risk pregnancies and associated factors in the city of Sao Paulo, Brazil. This was an evaluative study of 689 pregnant women referred from primary care (PHC) to specialized care in 2016. The type of PHC model was used as the main independent variable: family health units (USE), bask health units (UBS), and UBS/mixed. Multiple logistic regression models with forward selection were used for the outcomes early initiation of prenatal care and shared follow-up between specialized care and PHC: Referral by a USF was associated with higher odds of early initiation of prenatal care and shared follow-up between specialized care and PHC. Independently of the type of PHC, there were associations between early initiation of prenatal care and white skin color, and between shared follow-up between specialized care and PHC and having received a home visit. The results demonstrate the importance of services organized according to the USF model, which conducts home visits and is attuned to the implicit vulnerabilities in pregnant women's individual characteristics.
Keywords: Health Evaluation; Prenatal Care; Integrality in Health; Health Services Accessibility; Primary Health Care